Stability of addictive drugs in blood samples in storage - Hjálmar Arnar Hjálmarsson 1995- (2020)
In Iceland, a few thousand tests are done each year on the blood samples gathered from individuals suspected of driving under the influence (DUI) of psychoactive drugs. In the year 2019, around seven thousand tests were done on samples tied to suspected DUI cases. Despite these numbers, no systematic studies have been conducted on the stability of analytes such as amphetamine, methamphetamine, cocaine, diazepam, 3,4-methylenedioxymethamphetamine (MDMA), morphine, and delta-9-tetrahydrocannabinol (THC). The main objective of this thesis was to analyse and evaluate the stability of psychoactive drugs in blood while being stored for extended periods at -20°C. Samples were collected from the Department of Pharmacology and Toxicology (DPT). Concentrations of these samples were reanalysed using ultra-performance liquid chromatography tandem mass spectrometry (UPLC-MS/MS) and gas chromatography mass spectrometry (GC-MS) and their degradation calculated based upon the results of their previous measurements. The result of this study found that all the analytes remained relatively stable while in storage and all the samples can potentially be stored for a longer time at -20°C than the usual two years. Amphetamine and methamphetamine showed no signs of degradation after 18 months of storage though methamphetamine showed slightly more signs of degradation in comparison to amphetamine. Diazepam experienced degradation of between 5-10% after 18 months of storage. Cocaine appears to experience the most degradation before being put into storage and degraded about 40-50% before being frozen. Cocaine samples seem to remain stable while in storage at -20°C. THC appeared to degrade by about 5% every three months while in storage at -20°C. This study was unable to verify the stability of MDMA, methylphenidate, and morphine samples due to unforeseen circumstances (COVID-19). Still, preliminary results indicate that samples containing morphine are stable up until six months of storage at -20°C with no measurable signs of degradation. ...